Students' Verbal Thinking Structure in Solving Geometry Problems: Interaction Analysis on Procedural, Disputational, and Exploratory - Nurrahmah, Nurrahmah; Syarifudin, Syarifudin (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Yogyakarta, 2025)
This study aims to describe students' verbal thinking structure in solving geometry problems through interaction analysis in procedural, disputational, and exploratory activities. This research used a qualitative approach with a case study method, involving five grade VIII students who were selected based on their verbal communication and academic abilities. Data were collected through video recordings of group discussions, which were then transcribed and analyzed based on students' verbal interaction patterns. The results showed that in procedural activities, students tend to follow the solution steps without in-depth analysis and only exchange information instructionally. In disputational activities, there are differences of opinion and defense of arguments, which encourage students to be more critical in evaluating solutions. Meanwhile, exploratory activities allow students to ask questions, test hypotheses, and reflect more deeply on solutions. This pattern of interaction development supports Vygotsky's Zone of Proximal Development (ZPD) theory, where social interaction plays a role in promoting students' cognitive development. This finding indicates that verbal interaction in geometry learning not only helps students understand concepts, but also improves critical thinking and problem solving skills.